Racial differences and geographic variations in oral anticoagulation treatment among Medicare patients with non-valvular atrial fibrillation. - Larry R Jackson; Amiee Kang; Virginia Noxon; Nipun Atreja; Dionne M Hines; Melissa Hagan; Jenny Jiang; Brett D Atwater (PLoS ONE)
Introduction Use of oral anticoagulants (OACs) for stroke reduction in atrial fibrillation (AF) varies by race and geography within the United States. We seek to better understand the relationship between OAC underutilization, race, and US geography. Methods Patients with AF were selected from the US Centers for Medicare & Medicaid Services claims database from January 1, 2013, to December 31, 2016. The final population consisted of patients with 12 months of health plan enrollment before and after their index AF diagnosis, with a baseline CHAD2S2-VASc ≥2 and of either Black or White race (other races are underrepresented in the data). Among those with AF that met the inclusion criteria, patients who were prescribed warfarin or DOACs within 12 months after the index date were extracted. Each patient was assigned to a US county based on their 5-digit zip code and OAC use was stratified by race. Statistically significant differences were determined by student's t-test and chi-square. Results Of the 2,390,830 final patients, 94.1% were White and 5.9% were Black patients. Mean (SD) age and HASBLED scores were 78 (9) and 3.9 (1.2) respectively, for Black patients and 80 (9) and 3.3 (1.2), respectively, for White patients (p<0.0001). The mean (SD) CHAD2S2-VASc scores were 4.5 (1.9) for White patients, and 5.3 (1.9) for Black patients with p<0.0001, respectively. Black patients (vs White patients) had a higher non-treatment (no DOAC or warfarin) rate (56.1% vs 47.4%, p<0.0001) across the US which was particularly notable in the southeast. In addition, treatment rates were highly variable within each US state. Counties with dense population more frequently demonstrated significant differences by race than counties with sparse population. Conclusion Our study showed differences in the use of OACs across US counties and among various racial groups. These disparities highlighted the areas of unmet need for both Black and White patients.